Exploring strategies of teaching and classroom practices in response to challenges of inclusion in a Thai school: a case study - Kaur, Amrita; Noman, Mohammad; Awang Hashim, Rosna (Taylor & Francis Group, 2015)
The shift from special schools towards inclusive education is becoming increasingly prevalent across education systems around the world. However, the challenges this shift brings remain critical for developing nations where there is a huge chasm between policies and practices. This study used instrumental case study design to examine how a general education teacher strategised her teaching and classroom practices while accommodating a student with complex learning and behavioural disabilities within a regular classroom. Data collected through observations, in depth interviews and reflective journals suggested that the teacher made conscious efforts within limited resources to create strategies to help the student fit in the mainstream classroom. The strategies are discussed under socio-emotional, cognitive and physical categories. Implications for teachers' professional development are discussed.